Mechanisms involved in the transport of mercuric ions in target tissues - Bridges, Christy C. (Arch Toxicol, 2016)
Mercury exists in the environment in various forms, all of which pose a risk to human health. Despite guidelines regulating the industrial release of mercury into the environment, humans continue to be exposed regularly to various forms of this metal via inhalation or ingestion. Following exposure, mercuric ions are taken up by and accumulate in numerous organs, including brain, intestine, kidney, liver, and placenta. In order to understand the toxicological effects of exposure to mercury, a thorough understanding of the mechanisms that facilitate entry of mercuric ions into target cells must first be obtained. A number of mechanisms for the transport of mercuric ions into target cells and organs have been proposed in recent years. However, the ability of these mechanisms to transport mercuric ions and the regulatory features of these carriers have not been characterized completely. The purpose of this review is to summarize the current findings related to the mechanisms that may be involved in the transport of inorganic and organic forms of mercury in target tissues and organs. This review will describe mechanisms known to be involved in the transport of mercury and will also propose additional mechanisms that may potentially be involved in the transport of mercuric ions into target cells.